Comparative Analysis Among Integrated And Simplified Zvt Topologies Applied to Three-Phase Inverters - Beltrame, Rafael Concatto (2011)
This paper presents a peer comparison between the integration and simplification concepts of zero-voltage-transition (ZVT) circuits applied to voltage fed three-phase inverters used in industrial adjustablespeed drives. Initially, both concepts are defined and their main advantages and limitations are identified. Thereafter, a comparison is made between two selected topologies, considering modulation strategies, main and auxiliary circuit losses and the harmonic content of the inverter output voltage. It is demonstrated that when the load demands a voltage with low harmonic content, the simplified ZVT topologies are recommended and when the number of components is the main concern, the integrated ZVT topologies may be the best choice. Finally, experimental results for the selected topologies operating at 1.5 kW and 20 kHz are presented in order to confirm the comparative analysis carried out. The simplified ZVT topology presented an efficiency of 98.1% at nominal operation while the integrated ZVT topology presented an efficiency of 97.2% at the same condition.